Jeff Niederdeppe: Persuasion and Strategy Research in Health Communication - Liu, Zhenshuai (The Journal of Medicine, Humanity and Media, 2026)
Jeff Niederdeppe has long been deeply engaged in the fields of persuasion research and policy research, establishing himself as a renowned figure in empirical research within health communication. His work, aimed at achieving health equity, is characterized by distinct features in research positioning, theoretical application, and practical orientation. In terms of research positioning, he focuses on the "communication-policy-health" chain, conducting studies on diverse health topics such as tobacco control and obesity prevention. Theoretically, he adopts a problem-solving orientation, integrating multidisciplinary theories like narrative theory and inoculation theory, forming an academic logic of "theoretical integration-strategy design-dynamic interaction-effect optimization." Practically, his research yields a wealth of policy recommendations and practices that are precise and actionable, creating a complete cycle of "research findings-practical strategies-policy translation," providing strong support for the formulation and implementation of health policies. His research propels health communication towards greater policy relevance and practical significance, with future explorations potentially focusing on cutting-edge issues such as digital media and artificial intelligence.